2021
DOI: 10.1016/j.jpsychires.2021.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on involuntary and urgent inpatient admissions for psychiatric disorders in a German-wide hospital network

Abstract: The impact of COVID-19 on urgent and involuntary inpatient admissions, as well as coercive measures, has not been assessed so far. A retrospective study was performed analyzing claims data for inpatient psychiatric admissions between 2018 and 2020 (total n = 64,502) from a large German Hospital network. Whilst the total number of urgent admissions decreased in 2020 (12,383) as compared to 2019 (13,493) and 2018 (13,469), a significant increase in the percentage of urgent admissions was observed in 2020 (62.9%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 22 publications
16
25
1
Order By: Relevance
“…As the restrictions were intensive and prolonged in the jurisdiction in which study was conducted, it may be less surprising that the main findings of this study relate to the dramatically increased admission rates and involuntary admission orders. This study also replicates the findings from Switzerland and Germany, which also found that involuntary admission increased during the COVID-19 pandemic, although this related to all psychiatric presentations and not just psychotic disorders (Ambrosetti et al, 2021; Fasshauer et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…As the restrictions were intensive and prolonged in the jurisdiction in which study was conducted, it may be less surprising that the main findings of this study relate to the dramatically increased admission rates and involuntary admission orders. This study also replicates the findings from Switzerland and Germany, which also found that involuntary admission increased during the COVID-19 pandemic, although this related to all psychiatric presentations and not just psychotic disorders (Ambrosetti et al, 2021; Fasshauer et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The data suggest that the most severely ill patients continued to receive care, if necessary, on an involuntary basis, while less severely ill patients tended to avoid hospital care themselves or were not admitted due to the very restrictive case policy of hospitals. A similar development was observed in most medical specialties (9,10). Notwithstanding the fact that these longitudinal observational data do not allow for causal inferences in their nature, with respect to the use of coercion, we are not aware of any other explanation for this State-wide phenomenon.…”
Section: Discussionsupporting
confidence: 79%
“…A total of 84% of the institutions reported that they had established special wards or spaces for providing care for patients with SMI and comorbid SARS-CoV-2 infection, but that these areas were not used much because the first high incidence phase in Germany was not as severe as expected ( 10 ). The studies of routine data from a German psychiatric hospital network reported an overall decrease in emergency hospital admissions during this phase but an increase in the proportion of involuntary and urgent admissions ( 11 , 12 ). The evidence also hints at significant reductions in utilization in the German outpatient mental healthcare system during the first wave of the pandemic: For example, in March 2020, the number of individual psychotherapy cases decreased by 23%, and in April 2020, the number of psychiatric treatment cases, as measured by case-based lump sum payments, decreased by 30% and the number of group therapy cases decreased by as much as 60% ( 13 ).…”
Section: Introductionmentioning
confidence: 98%